Pola Sebaran dan Strategi Kebijakan Pengendalian Kebakaran Hutan dan Lahan Di Provinsi Sumatera Barat - Hendrio Fadly; Aldri Frinaldi; Dasman Lanin; Rembrandt Rembrandt (Jurnal Sains dan Ilmu Terapan, 2024)
Forest and land fires in Indonesia are recurring events and have a major impact on the environment, public health and the economy. Forest and land fires have also occurred in West Sumatra Province in the last five years. This research aims to look at the distribution pattern of forest and land fires and policy strategies for dealing with forest and land fires in West Sumatra Province. To see the distribution pattern of forest and land fires, this is done by processing indicative data on the area burned in West Sumatra Province in 2019-2023 which is overlaid with administrative area maps, forest area maps, and land use maps, as well as the distribution of times of forest and land fire incidents. Meanwhile, the policy strategy for dealing with forest and land fires is carried out using an Interpretative Structural Modeling (ISM) approach.